2020
DOI: 10.1097/psy.0000000000000854
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anxiety in Patients With Persistent Atrial Fibrillation Undergoing Elective Cardioversion: An Observational Study

Abstract: Objective Anxiety is often present among patients with atrial fibrillation (AF). This condition has been associated with greater symptom severity and worse quality of life in these patients. However, the influence of anxiety on the risk of AF recurrence is not well known. We aimed to define the level of anxiety in patients with persistent AF undergoing elective cardioversion (EC) and determine whether there is an association between anxiety and the risk of early AF recurrence after EC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Finally, no significant heterogeneity was found among the included cohort studies, which also reflected the consistency of the study design of the included cohorts. Previous studies also found that anxiety was independently associated with increased risks of early AF recurrence after cardioversion, 30 as well as AF incidence after cardiac surgery. 31 These findings, together with the findings from our meta‐analysis, may suggest that anxiety is a potential trigger of AF incidence or recurrence.…”
Section: Discussionmentioning
confidence: 86%
“…Finally, no significant heterogeneity was found among the included cohort studies, which also reflected the consistency of the study design of the included cohorts. Previous studies also found that anxiety was independently associated with increased risks of early AF recurrence after cardioversion, 30 as well as AF incidence after cardiac surgery. 31 These findings, together with the findings from our meta‐analysis, may suggest that anxiety is a potential trigger of AF incidence or recurrence.…”
Section: Discussionmentioning
confidence: 86%